2016
DOI: 10.1073/pnas.1604621113
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin-modifying genetic interventions suppress age-associated transposable element activation and extend life span in Drosophila

Abstract: Transposable elements (TEs) are mobile genetic elements, highly enriched in heterochromatin, that constitute a large percentage of the DNA content of eukaryotic genomes. Aging in Drosophila melanogaster is characterized by loss of repressive heterochromatin structure and loss of silencing of reporter genes in constitutive heterochromatin regions. Using next-generation sequencing, we found that transcripts of many genes native to heterochromatic regions and TEs increased with age in fly heads and fat bodies. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

19
201
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 190 publications
(226 citation statements)
references
References 37 publications
19
201
0
Order By: Relevance
“…Previously, it had been shown that a modest increase in Sir2 (7) or decrease in Adar (adenosine deaminase acting on RNA) activity (8), genetic interventions that increase heterochromatic repression, also lead to an extension in life span. In the present study, Wood et al (4) now show that these same life span-extending interventions also exhibited an age-dependent reduction in RTE activity. Extending these findings, Wood et al (4) show that two additional interventions predicted to maintain heterochromatic repression, increased expression of Su(var)3-9 or Dicer-2, resulted in both an age-dependent reduction in RTE activity and life span extension.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…Previously, it had been shown that a modest increase in Sir2 (7) or decrease in Adar (adenosine deaminase acting on RNA) activity (8), genetic interventions that increase heterochromatic repression, also lead to an extension in life span. In the present study, Wood et al (4) now show that these same life span-extending interventions also exhibited an age-dependent reduction in RTE activity. Extending these findings, Wood et al (4) show that two additional interventions predicted to maintain heterochromatic repression, increased expression of Su(var)3-9 or Dicer-2, resulted in both an age-dependent reduction in RTE activity and life span extension.…”
supporting
confidence: 77%
“…In the present study, Wood et al (4) now show that these same life span-extending interventions also exhibited an age-dependent reduction in RTE activity. Extending these findings, Wood et al (4) show that two additional interventions predicted to maintain heterochromatic repression, increased expression of Su(var)3-9 or Dicer-2, resulted in both an age-dependent reduction in RTE activity and life span extension. Taken together, these data suggest a robust relationship between repression of RTE activity and longevity.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…2b, side panel). We used a reporter of transposition for the endogenous gypsy retrotransposon ( gypsy-TRAP )924, a known target of Piwi in the ovary25, to detect transposition in fat body cells and found that piwi mutant fat bodies displayed significantly higher levels of gypsy transposition relative to controls (Fig. 2c).…”
Section: Resultsmentioning
confidence: 99%
“…The short interfering RNA pathway suppresses TEs in all tissues of plants and animals, whereas the activity of the Piwi-interacting RNA (piRNA) pathway is thought to be primarily restricted to the gonads of metazoans45. Loss or decline of these pathways results in genomic instability and cellular dysfunction caused by TE reactivation and transposition6789.…”
mentioning
confidence: 99%